Profile of Broiler Meat Retailers in Pinasungkulan raditional Market - Oroh, Franky N.S (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2025)
This research aims to determine the profile of broiler meat retailers at Pinasungkulan Market, Manado City. This research was conducted in November 2024 at the Pinasungkulan Karombasan Traditional Market, Manado City. This research is a survey research on broiler meat retailers. Determining respondents using the Purposive Sampling Method. The criteria for this research are broiler meat traders who sell every day at the Pinasungkulan Market in Manado City who have been selling for 2 years and do not raise their own broiler livestock. The research results show that the majority of broiler meat retailers are employed by women with a total of 8 people (58 .3%) and 4 men (33.3%). Broiler meat retailers are dominated by traders aged 31-40 years and 50 years with the same number, namely 4 people (33.3%), followed by traders aged 41-50 years with a total of 3 people (25%) , and only 1 trader aged 20-30 years with a percentage (8.3%). All broiler meat retailers at Pinasungkulan Karombasan Market have a high school/vocational school education level. A total of 5 broiler chicken meat retailers in the Pinasungkulan market have been selling for 10-20 years with a percentage of 41.7%. Retailers at Pinasungkulan Market, Manado City are charged a market levy from the market management of IDR 40,000 and IDR 70,000 every day